New contents and perspectives in the risk analysis of enterprises. (14th January 2008) - Falavigna, Greta
This paper presents a survey of techniques used for default risk analysis and it illustrates the reasons why a large number of researchers study the insolvency of firms. Firstly, there is an introduction on Basel II focusing on the first pillar and the new standards dictated by the New Basel Capital Accord (as reference, see: International Convergence of Capital Measurement and Capital Standards, Basel Committee on Banking Supervision, June 2004, Bank for International Settlements). This is followed by brief remarks about default definition and the following sections analyse different methods used for the study of default risk focusing on artificial neural network methodologies. The goal of this work is to understand if it is possible to use complex systems for the analysis of default risk and which model is the best.